High strain rate behavior of magnesium alloys under dynamic compressive loading at elevated temperature - Ang, Chiu Lee (2014)
The use of magnesium alloys in the automobile industry has seen a rising trend due to its lightweight property and high strength. In this report, AZ31B and its reinforced counterpart, AZ31B 1%SiC alloy are studied. The focus of this report is on the comparison of these two materials, as well as their behaviours under high strain rate of 700s-1 and 1400s-1 at elevated temperatures of 100°C and 200°C. Compressive test were carried out using the Split Hopkinson Pressure Bars. It was observed that AZ31B 1%SiC has a higher maximum compressive strength than AZ31B, of which increasing temperature deteriorates this strength. However, the strain of AZ31B 1%SiC is compromised due to the presence of SiC particulates. Also, a low strain rate test was carried out on the Instron machine as a comparison to the high strain rate behaviour. Indeed, for both materials, the stress-strain behaviour differs for low and high strain rates. This indicates the unsuitability of the stress-strain behaviour of low strain rate test to be used for high strain rate application such as the automobile industry. The degree to which it differs is indicated by strain rate sensitivity, m, in which increasing temperature gives rise to higher sensitivity. Strain hardening occurs under loading and the degree to which the material hardens depends on the strain hardening exponent n. The n-value is higher for AZ31B and for both materials, the value decreases with increasing temperature. It is also observed that AZ31B is a better energy absorber and that energy absorption capability decreases with increasing temperature.